The Influence of Leadership Competencies and Organizational Culture on Work Motivation and its Impact on Employee Performance - Ricki Indriansyah Bagjana; Ratri Wahyuningtyas (Publikasi Indonesia, 2025)
XYZ Group faces several major challenges that hinder the achievement of optimal employee performance. The main problem faced is the low employee performance, where many employees do not meet the minimum performance standard set by the company. Employee work motivation is also a serious issue, as a large number of employees feel less motivated to reach the set performance targets. Additionally, leadership competencies does not meet company standards, with leadership competencies scores at various management levels being below the required threshold. The newly established formal organizational culture, initiated in early 2022, has caused personal culture to be more dominant and systematically integrated into the organization's daily life. This study aims to identify and analyze the influence of leadership competencies and organizational culture on work motivation and its impact on employee performance at XYZ Group. By understanding these relationships, effective solutions are expected to be found to enhance employee performance and motivation through the development of leadership competencies and the strengthening of organizational culture. The research method used is a descriptive quantitative approach with a population consisting of all XYZ Group employees, totaling 106 individuals. The sample was taken using a saturated sampling technique, where the entire population was included. Primary data were obtained through the distribution of questionnaires and analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method to test the relationships between the variables in this study. This research reveals that leadership competencies and organizational culture at XYZ Group have a positive and significant impact on employee motivation and performance. The higher the leadership competencies and the stronger the organizational culture implemented, the higher the employee motivation and performance. Work motivation also serves as an intervening variable that links leadership competencies and organizational culture with performance. Weaknesses in leadership competencies and organizational culture can lower employee motivation and performance, making it essential for XYZ Group to enhance leadership competencies and strengthen organizational culture to further increase employee motivation and improve performance